MODERN TRENDS IN TEACHING FOREIGN LANGUAGES - Yunusova, Nodira (Educational Research in Universal Sciences, 2023)
This article explores modern trends in teaching foreign languages, focusing on key developments shaping language education. Topics covered include the integration of technology, blended learning models, task-based language teaching, cultural competence, individualized instruction, and Content and Language Integrated Learning. The essay emphasizes the evolving nature of language education, driven by technological advancements, cognitive research, and a growing emphasis on communicative competence.